Constitutional Law: Implikasi Bentuk Negara, Bentuk Pemerintahan dan Sistem Pemerintahan Terhadap Sistem Bernegara Federasi Rusia - Yunus, Nur Rohim (BULETIN ADALAH, 2021)
The Russian Federation is a federal state governed by a presidential system. Russia, functioning as a federation, encompasses a total of 85 federal subjects, each possessing varying degrees of autonomy. These levels of autonomy encompass republics, krais, oblasts, and autonomous districts. The executive branch of the Russian government is headed by a President who is elected directly by the populace and possesses extensive administrative authority. In addition to the aforementioned, there exists a Prime Minister who assumes the responsibility of executing governmental policies and overseeing the coordination of the cabinet. The Russian system of governance ensures a seamless integration of presidential and parliamentary components, facilitated by the presence of the Federal Assembly as a representative body that serves to maintain a balance of executive authority.